Insights into the immunomodulatory regulation of matrix metalloproteinase at the maternal-fetal interface during early pregnancy and pregnancy-related diseases - Jing, Mengyu; Chen, Xi; Qiu, Hongxia; He, Weihua; Zhou, Ying; Li, Dan; Wang, Dimin; Jiao, Yonghui; Liu, Aixia (Frontiers in Immunology, 2023)
Trophoblast-metaphase immune cellinteractions are central events in the immune microenvironment at the maternal-fetal interface. Their abnormalities are potential causes of various pregnancy complications, including pre-eclampsia and recurrent spontaneous abortion(RSA). Matrix metalloproteinases(MMPs) are highly homologous, zinc(II)-containing metalloproteinases closely associated with processes such as vascular remodeling and tissue remodeling at the maternal-fetal interface. However, the interaction mechanisms between MMPs and the immune microenvironment remain unelaborated. Here we discuss the key roles and potential mechanisms of MMPs with the immune microenvironment in the embryo implantation process and pregnancy-related diseases, which may contribute to understanding the establishment and maintenance of normal pregnancy and provide new therapeutic strategies. In addition, we outline the physiological roles of MMPs and pregnancy-related hormones (estrogen, progesterone, etc.) and their receptors during cyclic changes in the endometrium. Recent studies have shown that several matrix metalloproteinase inhibitors (MMPIs) effectively prevent invasive vascular disease by modulating the activity of MMPs. We summarize the main findings of these studies and suggest the possibility of MMPIs as emerging biomarkers and potential therapeutic targets for a range of complications induced by abnormalities in the immune microenvironment at the maternal-fetal interface. However, MMPs and MMPIs remain challenging, and more recent mechanistic functional studies are needed for the future immunotherapy of pregnancy-related diseases due to immune tolerance disorders.